Efeitos da inativação fotodinâmica e sua combinação com antibióticos contra Streptococcus spp - Gonçalves, Isabella Salgado (Universidade Federal de São Carlos, 2025)
Antimicrobial resistance is an escalating concern in global health, undermining the effectiveness of conventional treatments and necessitating the development of new therapeutic strategies. In this context, photodynamic inactivation (PDI) emerges as a promising technique due to its high microbial elimination capacity. This study aimed to evaluate PDI protocols for inactivating bacteria of the Streptococcus genus mediated by curcumin (CUR), as well as to investigate the effects of combining it with different antibiotics (ATBs), and to assess the technique’s ability to alter bacterial susceptibility to ATBs. The effect of PDI on both sensitive and resistant strains was analyzed using different CUR concentrations. The minimum inhibitory concentration (MIC) was determined for amoxicillin (AMO), ceftriaxone (CEF), and erythromycin (ERI). A time-kill curve was performed with these three ATBs, followed by the subsequent application of PDI after 3h, 6h, 9h, and 12h of incubation with the ATBs, at different CUR concentrations. Finally, consecutive cycles of PDI were applied to the bacteria to identify changes in MIC values. The results showed that CUR-mediated PDI is an effective technique against Streptococcus, capable of eliminating even resistant strains. Subsequent application of PDI after incubation with ATBs enhanced the antimicrobial effect of AMO and CEF against S. pneumoniae after 9 hours of incubation, increasing the antimicrobial activity by up to 2.8 log CFU/mL relative to CEF alone. Consecutive application of PDI reduced the MIC of AMO by half for S. pneumoniae and by a factor of 128 for S. pyogenes. Although parameters should be further investigated, the findings of this research suggest that CUR-mediated PDI can enhance the efficacy of existing antimicrobial treatments, standing out as an effective alternative or adjunctive strategy against major pathogens and potentially contributing to the fight against antimicrobial resistance.
Effects of photodynamic inactivation and its combination with antibiotics against Streptococcus spp
Keywords: Resistência antimicrobiana; Inativação fotodinâmica; Streptococcus; Suscetibilidade antimicrobiana; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA